Editing homologous copies of an essential gene affords crop resistance against two cosmopolitan necrotrophic pathogens. Issue 11 (26th July 2021) - Zhang, Xuekun; Cheng, Jiasen; Lin, Yang; Fu, Yanping; Xie, Jiatao; Li, Bo; Bian, Xuefeng; Feng, Yanbo; Liang, Weibo; Tang, Qian; Zhang, Hongxiang; Liu, Xiaofan; et al.
Abstract: Sclerotinia sclerotiorum and Botrytis cinerea are typical necrotrophic pathogens that can attack more than 700 and 3000 plant species, respectively, and cause huge economic losses across numerous crops. In particular, the absence of resistant cultivars makes the stem rot because of S. sclerotiorum the major threat of rapeseed ( Brassica napus ) worldwide along with Botrytis . Previously, we identified an effector‐like protein (SsSSVP1) from S. sclerotiorum and a homologue of SsSSVP1 on B. cinerea genome and found that SsSSVP1 could interact with BnQCR8 of rapeseed, a subunit of the cytochrome b‐c1 complex. In this study, we found that BnQCR8 has eight homologous copies in rapeseed cultivar Westar and reduced the copy number of BnQCR8 using CRISPR/Cas9 to improve rapeseed resistance against S. sclerotiorum . Mutants with one or more copies of BnQCR8 edited showed strong resistance against S. sclerotiorum and B. cinerea . BnQCR8 ‐edited mutants did not show significant difference from Westar in terms of respiration and agronomic traits tested, including the plant shape, flowering time, silique size, seed number, thousand seed weight and seed oil content. These traits make it possible to use these mutants directly for commercial production. Our study highlights a common gene for breeding of rapeseed to unravel the key hindrance of rapeseed production caused by S. sclerotiorum and B. cinerea . In contrast to previously established methodologies, our findings provide a novel strategy to develop crops with high resistance against multiple pathogens by editing only a single gene that encodes the common target of pathogen effectors.